1997
DOI: 10.3171/foc.1997.2.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode-guided posteroventral pallidotomy for treatment of Parkinson's disease: postoperative magnetic resonance imaging analysis

Abstract: The authors report the postoperative magnetic resonance (MR) imaging findings in 36 patients with advanced Parkinson's disease who underwent unilateral microelectrode-guided posteroventral pallidotomy. The lesions were placed within 1 mm of the ventral border of the globus pallidus internus (GPi) to include pallidothalamic outflow pathways. Sequential MR studies were obtained within 1 to 3 days postoperatively and at 6-month follow-up examination. Thirty-four (94%) of the 36 patients enjoyed sustained moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 36 publications
3
60
0
Order By: Relevance
“…Krauss et al 34 reported a somewhat similar result in patients who underwent medial pallidotomy. The acute-phase aspect on T2-weighted MRI images was of a three-concentric-zone lesion: a hyperintense inner zone, a hypointense middle zone (thought to represent hemorrhagic coagulation necrosis) and a hyperintense outer zone (thought to correspond to edema), involved by additional perilesional edema, with a signal not as intense as the lesion outer zone; the late-phase aspect was of a hyperintense lesion.…”
Section: Safety and Efficacysupporting
confidence: 64%
See 3 more Smart Citations
“…Krauss et al 34 reported a somewhat similar result in patients who underwent medial pallidotomy. The acute-phase aspect on T2-weighted MRI images was of a three-concentric-zone lesion: a hyperintense inner zone, a hypointense middle zone (thought to represent hemorrhagic coagulation necrosis) and a hyperintense outer zone (thought to correspond to edema), involved by additional perilesional edema, with a signal not as intense as the lesion outer zone; the late-phase aspect was of a hyperintense lesion.…”
Section: Safety and Efficacysupporting
confidence: 64%
“…The MRI aspect of a radiofrequency lesion was first described by Tomlinson et al, cited by Krauss et al 34 , in patients submitted to ventrolateral thalamotomy. Krauss et al 34 reported a somewhat similar result in patients who underwent medial pallidotomy.…”
Section: Safety and Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-dyskinetic effect of pallidotomy is considered the function of normalizing the pattern of firing of GPI (Guridi et al, 2008). The optimal lesion location within the GPI has been variously argued to be anteromedial (Gross et al, 1999) and posteroventral (Krauss et al, 1997).…”
Section: Pathophysiology Of Drug-induced Dyskinesias 99mentioning
confidence: 99%